2002
DOI: 10.1038/sj.bjc.6600337
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of combination chemotherapy with gemcitabine and oral UFT for advanced non-small cell lung cancer

Abstract: A phase I study was carried out to determine the optimal dose and administration schedule for combined UFT plus gemcitabine therapy in patients with non-small cell lung cancer. Twenty-four patients (including 11 patients previously treated with cisplatin as the key drug) received oral UFT 400 mg m 72 on days 1 to 14 with intravenous infusions of gemcitabine (800 mg gemcitabine on days 8 and 15. Eight of the 24 patients achieved partial response. The combination chemotherapy UFT and gemcitabine was well tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…The overall response rate of the present trial using UFT and gemcitabine was 41%. In a phase I trial of this combination chemotherapy, the response rate of patients without prior chemotherapy was also reported to be 45% (Seto et al, 2002). This high antitumour effect may lend support to the sequence of administration of UFT and gemcitabine.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The overall response rate of the present trial using UFT and gemcitabine was 41%. In a phase I trial of this combination chemotherapy, the response rate of patients without prior chemotherapy was also reported to be 45% (Seto et al, 2002). This high antitumour effect may lend support to the sequence of administration of UFT and gemcitabine.…”
Section: Discussionmentioning
confidence: 86%
“…In our prior phase I trial, the combination chemotherapy of UFT plus gemcitabine was found to be feasible (Seto et al, 2002). The most appropriate schedule and dosing was 200 mg m À2 of UFT b.i.d for 14 consecutive days with 900 mg m À2 gemcitabine on days 8 and 15.…”
mentioning
confidence: 99%
“…These results suggested that administration of UFT in combination with gemcitabine had at least some activity against advanced pancreatic cancer. Although the response rate of non-small cell lung cancer patients to UFT as a single agent was reported to be only 6-8%, a combination chemotherapy of UFT and gemcitabine demonstrated a 33% response rate and an extremely low incidence of adverse events in a phase I study [16] . While both UFT and gemcitabine inhibit DNA synthesis, UFT inhibits thymidylate synthase and gemcitabine causes DNA chain termination.…”
Section: Discussionmentioning
confidence: 99%
“…Major treatmentrelated adverse events other than hematologic toxicity were gastrointestinal symptoms such as anorexia and nausea. In a Japanese phase I study with advanced nonsmall cell lung cancer patients, a 3-weekly combination therapy of oral UFT 400 mg/m 2 per day for 14 days and gemcitabine 900 mg/m 2 on days 8 and 15 was shown to be well tolerated [16] . In the present trial, at the recommended oral UFT and gemcitabine doses of 400 mg per day for 14 days and 1,000 mg/m 2 , respectively, 3 patients received two cycles or more of chemotherapy without dose reduction or delay.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of gemcitabine combined with 5-FU has been relatively well established based on several phase I and II trials which reported that the combination therapy is superior to gemcitabine or 5-FU alone [14, 15, 16, 17]. In a Japanese phase I study, the combination therapy with gemcitabine and oral UFT was shown to be tolerable in advanced non-small cell lung cancer patients [22]. The efficacy and low toxicity of the regimen were also shown in advanced colorectal carcinoma and pancreatic cancer patients in Spanish phase II trials [23, 24].…”
Section: Discussionmentioning
confidence: 99%